IMPLEMENTASI MULTIPLE INTELLEGENCES PADA PENDIDIKAN BAHASA ARAB DI MADRASAH TSANAWIYAH MIFTAHUL ULUM BESUKI - El Fuadi, Muhammad Basiq; Baidhowi, M Kholil; Imron, Mohammad (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
Howard Gardner's concept of Multiple Intelligences suggests that each individual has different intelligences, developed in various ways. Based on this concept, the Arabic language education learning design at Madrasah Tsanawiyah Miftahul Ulum Besuki is designed by taking into account the intelligence possessed by students, so that learning can be adjusted. Focusing on the implementation of Arabic Language Education as a research objective, qualitative research methods with a case study approach were applied. Data collection techniques were carried out using observation, documentation and in-depth interviews. The sources of information for this research are the school principal, head of curriculum, head of public relations, Arabic language education teachers and students. Validation of research data is triangulation. Data analysis techniques consist of data collection, data presentation, data condensation, and drawing conclusions. Research findings show increased student involvement in learning in Arabic language education learning design at Madrasah Tsanawiyah Miftahul Ulum Besuki using the Multiple Intelligence concept approach: (1) Identification of linguistic, logical-mathematical, visual-spatial, kinesthetic, musical, interpersonal and intrapersonal intelligence. (2) Selecting the right learning method for each intelligence. (3) Integration of intelligence between different intelligences in learning. (4) The use of technology in learning can also help increase student involvement. It is hoped that the results of this research can be adopted in designing Arabic language education learning designs using the Multiple Intelligences concept approach, understanding students' intelligences and choosing learning methods that suit these intelligences. Thus, learning is more effective and student involvement in learning increases.